Mimetic failure: Politics, prayer and possession. Issue 1 (2nd January 2016) - Ghassem-Fachandi, Parvis
Abstract : In the micro-politics of community and neighborhood practice, formal Muslim prayer ( namaz ) frequently becomes juxtaposed to trance, possession or other dissociative states of consciousness. In the latter states, a subject becomes overwhelmed by an encounter with otherness and reacts on the basis of an economy of affect. In India such affective encounters are traditionally articulated allegorically in cultural forms that actively negotiate alterity. Specifically, the afflicted are considered "possessed" ( hajri ) and ritual specialists apply means of exorcism by naming the afflicting agent that has caused the disturbance. What happens, however, when a subject is overwhelmed by an encounter with an other, yet remains without any means to account for this experience? What happens when particular responses to feeling overwhelmed are no longer available or legitimate? Through ethnographic accounts of encounters, this paper first explicates encounters involving an overwhelming experience with difference in Africa and India in the 1950s that resulted in mimetic play, and then offers accounts of encounters of overwhelming experience in contemporary India in which alterity seemed absent and mimetic play failed.